Mast Cell Leukaemia: c-KIT Mutations Are Not Always Positive. (10th September 2012) - Joris, Magalie; Georgin-Lavialle, Sophie; Chandesris, Marie-Olivia; Lhermitte, Ludovic; Claisse, Jean-François; Canioni, Danielle; Hanssens, Katia; Damaj, Gandhi; Hermine, Olivier; Hamidou, Mohammed
Abstract : Mast cell leukemia (MCL) is a rare and aggressive disease with poor prognosis and short survival time. D816V c-KIT mutation is the most frequent molecular abnormality and plays a crucial role in the pathogenesis and development of the disease. Thus, comprehensive diagnostic investigations and molecular studies should be carefully carried out to facilitate the therapeutic choice. A MCL patient's case with rare phenotypic and genotypic characteristics is described with review of major clinical biological and therapeutic approaches in MCL.